Blood-based tumor biomarkers in lung cancer for detection and treatment - Mamdani, Hirva (Transl Lung Cancer Res, 2017)
The therapeutic landscape of lung cancer has expanded significantly over the past decade. Advancements in molecularly targeted therapies, strategies to discover and treat resistance mutations, and development of personalized cancer treatments in the context of tumor heterogeneity and dynamic tumor biology have made it imperative to obtain tumor samples on several different occasions through the course of patient treatment. While this approach is critical to the delivery of optimal cancer treatment, it is fraught with a number of barriers including the need for invasive procedures with associated complications, access to limited amount of tissue, logistical delays in obtaining the biopsy, high healthcare cost, and in many cases inability to obtain tissue because of technically difficult location of the tumor. Given multiple limitations of obtaining tissue samples, the use of blood-based biomarkers (“liquid biopsies”) may enable earlier diagnosis of cancer, lower costs by avoiding complex invasive procedures, tailoring molecular targeted treatments, improving patient convenience, and ultimately supplement clinical oncologic decision-making. In this paper, we review various blood-based biomarkers including circulating tumor cells (CTCs), circulating tumor DNA (ctDNA), tumor derived exosomes, tumor educated platelets (TEPs), and microRNA; and highlight current evidence for their use in detection and treatment of lung cancer.